Development and Testing of a Fast-Acting, 8-Bit, Digital Throttle for Hybrid Rocket Motors - Stephen A. Whitmore (Fire)
The potential for throttle control of hybrid rocket systems has long been known as a potential advantage for a variety of applications. Because only a single flow path is controlled, theoretically, hybrids should be significantly easier to throttle than bipropellant systems. Unfortunately, the slow response times and nonlinearity of traditional position-control valves have limited practical applications of hybrid throttling. This paper presents an alternative throttling system where the oxidizer flow path is broken into multiple streams, with each flow path controlled by a solenoid-operated on/off valve. The parallel paths allow significantly faster and more precise control than can be achieved using a single position-control valve. The achievable thrust levels are limited only by the size and number of components in the valve cascade. The 8-bit digital throttle system, developed by Utah State University’s Propulsion Research Lab, uses commercial, off-the-shelf components. The throttle system was tested using a 200-N hybrid rocket motor, burning gaseous oxygen, and ABS plastic as propellants. The testing campaign of more than 50 hot fires has demonstrated multiple profiles, including deep throttle ramps, multistep boxcars, and sine waves at frequencies varying from 0.25 to 1-Hz. Comparisons to analytical models are also presented, showing good agreement. Fourier-transform spectra demonstrating the total-system, frequency response are also presented.